Content marketing strategies, accounting and taxation of blogger activities in Ukraine - Yasyshena, Valentyna; Dolyuk, Alla; Bondaryeva, Tetyana (Herald of Economics, 2023)
Introduction. Internet marketing today is one of the most promising areas of marketing development in Ukraine. Blogging as a component of Internet marketing is actively developing and brings significant profits to bloggers. Since blogging is an economic activity, it needs proper reflection in the field of accounting and taxation with proper development of relevant provisions of domestic legislation.The purpos of the article is to analyze content marketing strategies in Internet literature using the example of the content novel «The Age of Glory and Hope» by Evgeny Litvak, to improve accounting and taxation procedures related to blogging activities, and to outline the prospects for its conduct in Ukraine.Research methods. In the research process, in particular, the following methods were used: analysis and synthesis - to study the object and subject of research; abstract- logical - for theoretical generalizations and formulation of conclusions; constructive and experimental - to form a decision with the help of analytical support; tabular – for a visual representation of the formation of pricing of paintings.Research results. The content marketing strategy was analyzed using the example of the network author’s works of «litweeks», it was proved that a successful marketing strategy allows you to get a good financial income, and therefore the opportunity to officially register your activity and pay taxes to the state budget. Prospects for the development of blogging activity in Ukraine are revealed. Procedures for accounting and taxation of blogging activities in Ukraine have been revealed. The main advantages for the socio- economic development of the state from the official activity of a blogger are outlined, and problematic areas in the formation of the official online business of Internet literature in Ukraine are identified.Results. The main provisions of this study in the form of proposals can provide a number of benefits for the official online business business in Ukraine. Staffing at the legislative level of blogger activity, accounting and taxation of bloggers is a significant contribution to the socio-economic development of the state, will help to increase the revenues to the state budget, harmonize the activity of the blogger and the employer and will become the key to social guarantees for bloggers. Increasing the attractiveness of the blogger profession will contribute to the development of this area of activity.Discussion. A successfully chosen marketing strategy (for example, Yevgeny Litvak’s writer’s blog) allows you to increase your popularity, establish a strong connection with the audience and attract new advertisers.If bloggers develop their activities and want to earn significant profits, they must account for the income they receive and pay taxes. An important factor in the cooperation of an advertiser with a blogger is taxation, which allows transparent reporting to the tax office and honest payment of taxes.During the consideration of procedures for accounting and taxation of operations and processes of blogger activity in Ukraine, it is proposed to add a separate KVED with the name «blogger activity». Changes should be made to the Tax Code of Ukraine and accounting and taxation conditions for blogging activities should be established.